(untitled) (Journal of the College of Languages (JCL), 2023)
The analysis of detective novels has taken different aspects. The linguistic analysis of them, for example, has tackled the linguistic systems of morphology, phonology, syntax, semantics, and pragmatics. In line with the linguistic analysis, this study explores the various pragmatic and stylistic devices realized through detective novels for the purpose of misdirecting and deceiving the reader. The problem is that when readers try to reach to the truth, they face difficulties. They might not reach to the right solution or infer wrong conclusions because writers use some techniques to hide the truth and mislead them. This study aims at examining these techniques and devices; namely, Grice’s Maxims and ambiguity as pragmatic devices on the one hand, and foregrounding, backgrounding, and focalization as stylistic devices on the other hand. It also aims to show the effect of these devices in a number of selected detective novels written by Agatha Christie and Arthur Conan Doyle. It is hypothesized that different stylistic strategies are used in detective novels for the purpose of misdirection and that foregrounding is the most frequently used one among these devices. It is also hypothesized that the rate of using pragmatic deception strategies is higher in Christie’s novels than in Doyle’s ones, especially the violations of Grice’s maxims, and that the two maxims of Quantity and Manner are more frequently violated than the other two maxims of Quality and Relevance. The findings of the study reveal that Christies’ style of writing is more mysterious than that of Doyle. The study also reveals that focalization, the violation of the two maxims of Quantity and Quality, and the utilization of ambiguous expressions which are also considered instances of violating the maxim of Manner are the most recurrent stylistic and pragmatic deception strategies respectively. Received on 9/5/2021 Accepted on 11/7/2021 Published on 2/1/2023